2005
DOI: 10.1063/1.2037847
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nitrogen with vacancy defects in N+-implanted ZnO studied using a slow positron beam

Abstract: ZnO crystals were implanted with N+, O+, and Al+, and co-implanted with O+∕N+ and Al+∕N+ ions. Positron annihilation measurements indicate introduction of vacancy clusters upon implantation. In the N+-implanted and Al+∕N+ co-implanted samples, these vacancy clusters are only partially annealed at 800°C, as compared with their entire recovery in the O+- and Al+-implanted samples at 800–900°C, suggesting a strong interaction between nitrogen and vacancy clusters. However, in the O+∕N+ co-implanted sample, most v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…Positron annihilation spectroscopy (PAS) suggested the existence of N O -V Zn complexes in N + -implanted ZnO crystals. This complex was stable even above 1000 °C [22]. Such a complex between N O and V Zn , would agree with the involvement of N O in the transition at ∼3.1 eV, reported by Georgobiani et al [18], as well as the participation of V Zn in the same transition as reported in [20] and [21].…”
Section: Contributed Articlesupporting
confidence: 87%
“…Positron annihilation spectroscopy (PAS) suggested the existence of N O -V Zn complexes in N + -implanted ZnO crystals. This complex was stable even above 1000 °C [22]. Such a complex between N O and V Zn , would agree with the involvement of N O in the transition at ∼3.1 eV, reported by Georgobiani et al [18], as well as the participation of V Zn in the same transition as reported in [20] and [21].…”
Section: Contributed Articlesupporting
confidence: 87%
“…Compared to the silicon substrate and the as-deposited ZnO samples, the noteworthy differences are the appearances of new Raman peaks in the ZnO samples after N-or Xe-ions bombardments: It was reported that the Raman mode at about 578 cm À1 may originate from defects related phonon mode [12], O-vacancies related stable complexes [13], or from the disorder-activated B 1 (high) silent mode [14] of w-ZnO. Considering that there are defects could only be introduced in the samples under 308 MeV Xe-ions irradiation, the observed peak at about 578 cm À1 (P 1 ) may originate from the defects or disorder phase produced in the samples.…”
Section: Resultsmentioning
confidence: 98%
“…This is seen in both undoped and Al/Ga-doped thin films 21,[26][27][28] as well as in studies in bulk crystals. [10][11][12]22,25 Clusters of vacancies in ZnO have been observed mainly in implantation studies 4,23,[29][30][31][32][33][34][35][36][37][38] and also after heavy irradiation. 21 These vacancy clusters have been shown to disappear (become unstable) in thermal treatments at temperatures of about 800°C, with a single exception: the N-implantation damage is stable up to at least 1000°C in ZnO.…”
Section: Discussionmentioning
confidence: 99%